2018
DOI: 10.14393/bj-v34n1a2018-36825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of gestation on fatty acid transporters mrna expression in bovine placenta

Abstract: ABSTRACT:The objective of the study was to evaluate the effect of time of gestation on fatty acid transporter mRNA expression in maternal and fetal bovine placenta. Placentas from twelve cows at different thirds of gestation (n=4 per third) were sampled at slaughter to measure FATP-1, FATP-4, FABP-1 mRNA concentration in maternal (caruncles) and fetal (cotyledons) side. Once the placenta was removed, 1cm 2 was dissected and, divided into caruncles and cotyledons, stored in sterile tubes, dropped into liquid ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Supplementing the maternal diet of ewes during the first 45 days of gestation with EPA and DHA tended to result in a greater abundance of FATP-1 mRNA transcript in the FL. The presence of FATP-1 was reported by Desantadina et al [27] during the initial two thirds of the gestation period in the caruncle area of the placenta of cattle and this finding is consistent with those of the present study. Feeding of diets containing greater amounts of fat lead to greater abundances of placental FATP-1 mRNA transcript compared with what is present in the placenta of animals fed standard diets [28], which may lead to increased transport of dietary fatty acids from the dam to the fetus.…”
Section: Discussionsupporting
confidence: 94%
“…Supplementing the maternal diet of ewes during the first 45 days of gestation with EPA and DHA tended to result in a greater abundance of FATP-1 mRNA transcript in the FL. The presence of FATP-1 was reported by Desantadina et al [27] during the initial two thirds of the gestation period in the caruncle area of the placenta of cattle and this finding is consistent with those of the present study. Feeding of diets containing greater amounts of fat lead to greater abundances of placental FATP-1 mRNA transcript compared with what is present in the placenta of animals fed standard diets [28], which may lead to increased transport of dietary fatty acids from the dam to the fetus.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, our result on FATP1 relative mRNA expression differs from the ones reported by Roque-Jimenez et al [ 11 ], where an increase in the relative abundance of this gene was observed after maternal omega-3 PUFA supplementation during early gestation in fetal liver; but are in accordance with what was reported by Nickles et al [ 3 ] when PUFA supplementation was fed in the last third of gestation, even though a Met supplementation was not used in this trial. Desantadina et al [ 64 ] observed FATP1 in bovine maternal side of placenta in the first two thirds of gestation. The changes observed in FATP1 relative mRNA expression suggest that FATP1 action in FA metabolism may be more important in early gestation.…”
Section: Discussionmentioning
confidence: 99%
“…In ruminant animals, it has been observed that the transfer of some unsaturated fatty acids appears to be restricted in the epithelial-vascular placenta, often resulting in a deficiency of these components in newborns [130]. In a study conducted by Desantadina et al [154] on the placenta of cattle, changes in mRNA expression were noted only for the fatty acid transport protein FATP-1. In early pregnancy, FATP-1 shows a higher expression on the fetal side compared to the maternal side.…”
Section: Importance Of Fa N-3 In Fetus Developmental Programming and ...mentioning
confidence: 99%